Harmonization of Goods/Services Procurement Arrangements in Villages with the National Legal System: A Study on the Application of Professionalism Principles in Village Procurement - Hermansyah (Journal of Law, Politic and Humanities, 2025)
Harmonizing village procurement regulations with the national legal system is an important need to create professional, transparent, and accountable governance. Procurement of goods and services in villages is regulated through regulations that provide flexibility according to local needs, but are not yet fully integrated with the national system that emphasizes competency standards, supervision, and principles of professionalism. This mismatch creates risks of maladministration, violations of the law, and uncertainty in the implementation of goods and services procurement in the village. This research aims to analyze the regulatory gaps and formulate harmonization measures. This research uses statutory and conceptual approaches to examine relevant legal rules and concepts of professionalism. The results show the need for a master regulation that integrates the procurement of goods and services in the village with the national system. Minimum standards of implementation, such as competency requirements for procurement actors, clearer monitoring mechanisms, and training and certification for village procurement actors, should be implemented to improve professionalism. In addition, the use of procurement agents can be a temporary solution for villages that lack human resources. This harmonization is expected to create legal certainty and efficiency, while supporting equitable village development without losing local flexibility.